Bercakap bahasa Arab Speak Arabic - Qais Faryadi bin Sadrudeen
This interactive Arabic conversational CD has been designed to help students, business people and travelers in improving their everyday communication skills. This CD consists of 20 lessons with selected topics of everyday usage. The vocabulary for each lesson enhances user's understanding of the dialogue.